IL-1β and IL-6 Upregulation in Children with H1N1 Influenza Virus Infection - Antonio Chiaretti; Silvia Pulitanò; Giovanni Barone; Pietro Ferrara; Valerio Romano; Domenico Capozzi; Riccardo Riccardi (Mediators of Inflammation)
The role of cytokines in relation to clinical manifestations, disease severity, and outcome of children with H1N1 virus infection remains thus far unclear. The aim of this study was to evaluate interleukin IL-1β and IL-6 plasma expressions and their association with clinical findings, disease severity, and outcome of children with H1N1 infection. We prospectively evaluated 15 children with H1N1 virus infection and 15 controls with lower respiratory tract infections (LRTI). Interleukin plasma levels were measured using immunoenzymatic assays. Significantly higher levels of IL-1β and IL-6 were detected in all patients with H1N1 virus infection compared to controls. It is noteworthy to mention that in H1N1 patients with more severe clinical manifestations of disease IL-1β and IL-6 expressions were significantly upregulated compared to H1N1 patients with mild clinical manifestations. In particular, IL-6 was significantly correlated with specific clinical findings, such as severity of respiratory compromise and fever. No correlation was found between interleukin expression and final outcome. In conclusion, H1N1 virus infection induces an early and significant upregulation of both interleukins IL1β and IL-6 plasma expressions. The upregulation of these cytokines is likely to play a proinflammatory role in H1N1 virus infection and may contribute to airway inflammation and bronchial hyperreactivity in these patients.